1993
DOI: 10.1038/hdy.1993.28
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of chromosome instability in cell suspensions of diploid, tetraploid and hexaploid wheats

Abstract: Chromosome instability was monitored' through time in cell suspensions of the diploids Triticum tauschii (the D genome donor) and T monococcum (the A genome donor), the tetraploids, T durum and T dicoccum (both AABB) and in the cultivars Copain and Sicco of hexaploid (AABBDD) breadwheat (T aestivum). Differences in stability were observed between the different ploidy levels and between species within the ploidy levels. The diploids were most stable, particularly T. tauschii, and the hexaploids were least stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
(20 reference statements)
0
7
0
1
Order By: Relevance
“…In a comparison of cell suspensions of diploid, tetraploid and hexaploid wheats, the diploids were found to be the most stable and the hexaploids the least stable, but genotype differences were evident within the ploidy levels (Winfield et al ., 1993) . Similarly, several reports indicate that somaclonal variation is minimal in regenerants of barley Karp et al, 1987 ;Ruiz et al ., 1992), but quite extensive in another diploid cereal, rye Linacero & Vazquez, 1992) .…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of cell suspensions of diploid, tetraploid and hexaploid wheats, the diploids were found to be the most stable and the hexaploids the least stable, but genotype differences were evident within the ploidy levels (Winfield et al ., 1993) . Similarly, several reports indicate that somaclonal variation is minimal in regenerants of barley Karp et al, 1987 ;Ruiz et al ., 1992), but quite extensive in another diploid cereal, rye Linacero & Vazquez, 1992) .…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of ploidy status performed by the aid of flow cytometry proved to be an efficient tool to detect the ploidy level of a plant, as reported (Dickson et al, 1992;Gantait et al, 2011a). It was reported that in comparison to the other higher ploidy levels (tetraploid or hexaploid) the diploids were found to be the most stable (Winfield et al, 1993). Yet, there are several reports on the extensive alteration of ploidy level in a number of diploid species (Karp et al, 1992;Linacero and Vazquez, 1992).…”
Section: Analysis By Flow Cytometrymentioning
confidence: 90%
“…Pretreatment and fixation of root tips and suspensioncultured cells for chromosome analyses were performed according to Winfield et al (1993). A minimum of 5 slides and 50 complete cells were examined per sample.…”
Section: Cytological Analysismentioning
confidence: 99%
“…Creso, 2n = 28; 7: aestivum cv. Sicco, 2n = 42) indicated that instability was related to the allohexaploid constitution of wheat (Bang 1990;Winfield et al 1993), with diploids being more stable than hexaploids.…”
Section: Introductionmentioning
confidence: 96%